Literature Review : Kajian Biologi Reproduksi pada Ikan Nila (Oreochromis Niloticus) di Perairan Indonesia - Dhea Rhamadini; Cut Putroe Safira Annika; Firdus Firdus; Muhammad Nasir; Zainal Abidin Muchlisin (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2024)
Tilapia (Oreochromis niloticus) has a number of favorable characteristics, such as reproducing easily, rapid growth, resistance to sub-ideal environmental conditions, and survival in high salt water. The purpose of this study is to conduct a comprehensive literature review on the reproductive biology of tilapia in Indonesian waters. This research method is in the form of secondary data which is used as the main source in the descriptive approach of literature review studies. The results showed that male tilapia grew faster than female tilapia, and female tilapia required a greater amount of energy for the maturation of its eggs. Female tilapia has a higher gonad maturity index than male tilapia in Indonesian waters. Types of tilapia vary. With a size of ± 3 mm, the diameter of tilapia eggs is very diverse.